2020
DOI: 10.1177/1059601120910848
|View full text |Cite
|
Sign up to set email alerts
|

Team Membership Change “Events”: A Review and Reconceptualization

Abstract: Driven by views of teams as dynamic systems with permeable boundaries, scholars are increasingly seeking to better understand how team membership changes (i.e., team members joining and/or leaving) shape the functioning and performance of organizational teams. However, empirical studies of team membership change appear to be progressing in three largely independent directions as researchers consider: (a) how newcomers impact and are impacted by the teams they join; (b) how teams adapt to member departures; or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 116 publications
(178 reference statements)
1
39
0
1
Order By: Relevance
“…Similarly, the temporal stability of team membership should be negatively related to temporal dynamism. When resources in the external team context demonstrate changes in valence, fast rates of change, and discontinuity, it becomes important for the team to change membership to ensure the team has the appropriate knowledge and expertise (e.g., Kozlowski et al, 1999; Mathieu et al, 2014; Trainer et al, 2020). For example, Chandler et al (2005) demonstrated that greater environmental dynamism contributes to more team membership changes.…”
Section: A Theoretical Framework For External Team Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the temporal stability of team membership should be negatively related to temporal dynamism. When resources in the external team context demonstrate changes in valence, fast rates of change, and discontinuity, it becomes important for the team to change membership to ensure the team has the appropriate knowledge and expertise (e.g., Kozlowski et al, 1999; Mathieu et al, 2014; Trainer et al, 2020). For example, Chandler et al (2005) demonstrated that greater environmental dynamism contributes to more team membership changes.…”
Section: A Theoretical Framework For External Team Contextsmentioning
confidence: 99%
“…Second, the temporal stability of the team should be lower when the external team context has greater munificence. First, teams can alter their composition to pursue different means-end paths with different combinations of skills over time (Hambrick & Finkelstein, 1987;Mathieu et al, 2014;Trainer et al, 2020). Second, members may seek other opportunities in the organization with a munificent external environment, as such opportunities may provide task This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Effects Of Context On Team Types and Compositionmentioning
confidence: 99%
“…Shared mental model theory (Cannon-Bowers, Salas, & Converse, 1993) suggests that teams that effectively use these common knowledge structures will be better able to quickly adapt to changing task and contextual demands. This may be particularly important in contexts in which teams are likely to encounter unexpected events on a regular basis, as their mental models may require frequent and rapid refinements (Trainer, Jones, Pendergraft, Maupin, & Carter, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shared mental model theory (Cannon-Bowers, Salas, & Converse, 1993) suggests that teams that effectively use these common knowledge structures will be better able to quickly adapt to changing task and contextual demands. This may be particularly important in contexts in which teams are likely to encounter unexpected events on a regular basis, as their mental models may require frequent and rapid refinements (Trainer, Jones, Pendergraft, Maupin, & Carter, 2020). Mathieu, Heffner, Goodwin, Salas, & Cannon-Bowers (2000) hypothesized that mental models in teams would converge over time as teams gained experience with the task and with each other but found that convergence of mental models in teams did not increase over time.…”
Section: Feedback and Teamworkmentioning
confidence: 99%
“…Further, much of the empirical work conducted on teams fails to include a dynamic view, including dynamic team membership ( Cronin, 2015 ). Recent conceptualizations of team membership change suggest each change functions as a specific “event” which may affect team functioning in different ways, depending on the novelty, disruptiveness, and critical nature of the change ( Trainer et al, 2020 ). From a methodological perspective, this stability of membership allows one to conclude that the relationships and effects under investigation are not confounded by any changes in the team’s composition and membership.…”
Section: Teams In Small Organizations: Conceptual Considerationsmentioning
confidence: 99%